2023
DOI: 10.52215/rev.bgs.2023.84.3.133
|View full text |Cite
|
Sign up to set email alerts
|

Posušje bauxites in Bosnia and Herzegovina: A source of critical raw materials and a paleoclimatic marker

Irena Peytcheva,
Šime Bilić,
Stoyan Georgiev
et al.

Abstract: The present study provides geochemical and geochronological data about Posušje bauxites in Bosnia and Herzegovina with the aim to characterize them as Critical Raw Materials (CRMs) sources and to put constraints on the time and genesis of the deposit. Boehmite is the bauxites’ main Al-bearing mineral, while gibbsite is a minor constituent. Hematite is the dominant Fe-phase, whereas goethite is rare. The chemical analyses indicate that the Al2O3 content ranges from 49.6 to 63.0 wt %, Fe2O3 varies from 16.5 to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…The ratio of gibbsite to boehmite varies from deposit to deposit, and in some deposits, boehmite is the only aluminium phase present. Recent petrographic, mineralogical and chemical investigations [20] have shown that the predominant Fe phase in all deposits is hematite, while goethite-rich bauxites are rare. Zircon, apatite and calcite were found as minor minerals.…”
Section: The Geology Of Bauxite Depositsmentioning
confidence: 98%
“…The ratio of gibbsite to boehmite varies from deposit to deposit, and in some deposits, boehmite is the only aluminium phase present. Recent petrographic, mineralogical and chemical investigations [20] have shown that the predominant Fe phase in all deposits is hematite, while goethite-rich bauxites are rare. Zircon, apatite and calcite were found as minor minerals.…”
Section: The Geology Of Bauxite Depositsmentioning
confidence: 98%